Contributions to teachers´s training and development: a view from an action-research perspective (Praxis Educativa, 2012)
In order for educational change to occur, the need to strengthen teachers and students. Reflexive processes is seen as fundamental. Yet, in previous papers that provide evidence of twelve years of research on Teacher Education, we have already accounted for the fact that reflective processes are not that easily activated. Since the development of LAD and its application to different reflective situations (LAD- Lesson Analysis Device- D.A.C in Spanish), both taking into account theory and practice, we have hypothesized about the existence of cultural restrictions that hinder reflection. Thus, this piece of research set three main objectives: to analyze cooperative action-research processes; to interpret cultural restrictions to reflection; and to characterize processes that facilitate reflection. To address this issue, we changed the scenario by giving up the perspective of supporting teachers. Development through training, to approaching it from the very post-graduation system, involving specialists in the process, through a network of action researchers. Seventy-five teachers organized in twenty-one groups and assisted by three specialists, engaged in the analysis and elucidation of every-day school problems, with the aim of improving their practice. Up to the present, we could identify three restrictions that could operate individually or in combination as internalized cultural dictates: a) thinking of only one possible practice (the minds uniform), which coincides with the official proposals;b) inducing a feeling of panic towards tradition (the loss of History); and  c) thinking about the subject to later dropping it, alluding to the grounds used by the new proposals or didactic models. These cultural restrictions may emerge as objects of reflective analysis in cooperative processes of action-research.
Keywords: teacher education; action; research; reflective processes; reflection facilitators; reflection restrictions